A new assessment of the circulation of Atlantic and Intermediate Waters in the Eastern Mediterranean. (November 2021) - Estournel, Claude; Marsaleix, Patrick; Ulses, Caroline
Graphical abstract: Highlights: A high resolution simulation is compared to 25, 000 Argo profiles and satellite SST. A clarification of the seasonal circulation of the last 8 years is proposed. New circulation patterns are highlighted in the southeast Levantine and Ionian Seas. Abstract: A simulation of the Mediterranean circulation between 2011 and 2020 at a resolution of 3–4 km in the Eastern basin was compared to vertical profiles and horizontal distributions of temperature and salinity from Argo profilers distributed throughout the basin. The comparison is marked by high temporal (∼0.9) and spatial (0.6–0.8) correlations and low biases. Comparisons of SST with satellite imagery have also shown strong similarities for numerous structures over a wide range of spatial scales. The simulation is used to describe the mean circulation of surface Atlantic Waters and Intermediate Waters in winter and summer. The surface circulation is cyclonic alongslope, stronger and more stable in winter. In summer, the current veins are sometimes interrupted and replaced by trains of eddies like in the South Ionian. In other cases, the current becomes very narrow and stuck to the coast as along the Ionian east coast or the Middle East coast. In winter, surface and Levantine Intermediate Waters exit from the Levantine mainly through the Aegean, while in summer, they exit westward south of Crete. The Aegean tends in summer to be isolated by eddies that develop on both sides of the Cretan Arc. The juxtaposition of Ierapetra, the Rhodes Gyre and the Mersa-Matruh Eddies produces a southward path across the Levantine basin at about 27 − 28°E which delimits a large cyclonic circulation to the east which tends to separate the two parts of the basin (west and east Levantine). Concerning the Levantine Intermediate Waters, the alongslope cyclonic circulation all around the Levantine basin in winter is no longer maintained in summer as a large anticyclonic circulation occupies the southeast of the basin. The intermediate waters entering the Ionian either through southern Crete in summer or through the Aegean in winter, are submitted to a strong northward, southward and even westward dispersion by Pelops and the nearby anticyclonic areas. The presence of recurrent anticyclones between 35 and 37°N along a band extending from west to east of the Ionian also produces a vertical dispersion of intermediate water. Finally, the circulation of intermediate water in the South Ionian is marked by an important seasonality with the presence in summer of a large anticyclonic circulation that seems to be wind induced and finally drives a secondary branch to the Sicily Channel. A climatology for the transport through the different straits is discussed and simplified representations of the circulation are proposed.